A Need Analysis on Developing English Interactive Multimodal E-Book Oriented to 21st Century Skills - Kholis, Adhan; Azmi, Ulul (Elsya : Journal of English Language Studies, 2023)
The need toward availability of online and electronic textbooks (e-books) in language teaching and learning in digital age and 21st century is very considerable. To design and develop an electronic book, teachers should consider all students’ needs. This study aimed to investigate and explore students’ English learning needs, wants, and difficulties of primary education on developing English interactive multimodal e-book integrated with the skills of 21st century including communication, collaboration, critical thinking, and creativity. The case study research design was used to deeply investigate and describe the students’ needs on development of English e-book. To collect data on the students’ necessities, difficulties, and wants for a primary English course design and skills, the researchers used interview and questionnaire. . The researcher interviewed one teacher and three students. For questionnaire, there were three main aspects asked: students’ necessity, wants, and difficulties totally consisting of sixteen questions. Documentation of the teaching and learning activities photos was collected and the data were analysed using qualitative and quantitative analysis. The results included (1) the students’ English skill was considered poor; they had little vocabulary mastery and low motivation toward learning English materials (2) the needs toward the 21st century skills to be included in e-book were very necessary to promote communication, critical thinking, and problem solving skills; (3) inserting various multimodal materials in each task of e-book was needed to increase students’ references, reading comprehension, and digital literacy, and (4) inclusion of various online activities like synchronous and asynchronous mode was highly demanded.